The Influence of Auditory Cues on Bodily and Movement Perception - Stanton, Tasha R.; Spence, Charles (Frontiers in Psychology, 2020)
The sounds that result from our movement and that mark the outcome of our actions typically convey useful information concerning the state of our body and its movement, as well as providing pertinent information about the stimuli with which we are interacting. Here we review the rapidly-growing literature investigating the influence of non-veridical auditory cues (i.e., inaccurate in terms of their context, timing, and/or spectral distribution) on multisensory body and action perception, and on motor behaviour. Inaccurate auditory cues provide a unique opportunity to study cross-modal processes: the ability to detect the impact of each sense when they provide a slightly different message is greater. Additionally, given that similar cross-modal processes likely occur regardless of the accuracy or inaccuracy of sensory input, studying incongruent interactions are likely to also help us predict congruent interactions. The available research convincingly demonstrates that perceptions of the body, of movement, and of surface contact features (e.g., roughness) are influenced by the addition of non-veridical auditory cues. Moreover, auditory cues impact both motor behaviour and emotional valence, the latter showing that sounds that are highly incongruent with the performed movement induce feelings of unpleasantness (perhaps associated with lower processing fluency). Such findings are relevant to the design of auditory cues associated with product interaction, and the use of auditory cues in sport performance and therapeutic situations given the impact on motor behaviour.